Is monetary integration economically viable in the Economic Community of West African States? - Olayode W. Agboola; Olaolu Richard Olayeni (West African Journal of Monetary and Economic Integration, 2022)
The introduction of a common currency in the Economic Community of West African States (ECOWAS) has been the subject of extensive research over the past couple of decades, with extant issues ranging from viability and feasibility to sustainability of monetary integration in the region. This study explores the economic viability of a West African monetary union by investigating the effectiveness of monetary policy as the opportunity cost of integration. Using the structural vector autoregressive (SVAR) estimation technique to analyze time series data from 1981 to 2021, the study finds no evidence of effective monetary policy in Nigeria, The Gambia, and the WAEMU while there is only weak evidence of effectiveness of monetary policy in Ghana, Sierra Leone, and Cabo Verde. The study concludes that an ECOWAS monetary union may be economically viable, provided that the region can leverage opportunities to deepen inter-regional trade to further strengthen the benefits, against the already low opportunity cost of integration in terms of a mostly ineffective independent monetary policy in the region. The study also recommends the incorporation of some form of 'monetization mechanism' for catering to negative output shocks in the absence of independent monetary policy.
Keywords: E52; E32; E58; F33; 330; Optimal Currency Area; Monetary Integration; Convergence Criteria; Monetary Policy Effectiveness; Business Cycle Synchronization